HIF‐1α/Actl6a/H3K9ac axis is critical for pluripotency and lineage differentiation of human induced pluripotent stem cells. Issue 4 (28th February 2020) - Cui, Peng; Zhang, Ping; Zhang, Yanmin; Sun, Lihua; Cui, Guanghui; Guo, Xin; Wang, He; Zhang, Xiaowei; Shi, Yu; Yu, Zhendong
Abstract: Pluripotent stem cells (PSCs) are important models for analyzing cellular metabolism and individual development. As a hypoxia‐inducible factor subunit, HIF‐1α plays an important role in maintaining the pluripotency of PSCs under hypoxic conditions. However, the mechanisms underlying the self‐renewal and pluripotency maintenance of human induced pluripotent stem cells (hiPSCs) via regulating HIF‐1α largely remain elusive. In this study, we found that disrupting the expression of HIF‐1α reduced self‐renewal and pluripotency of hiPSCs. Additionally, HIF‐1α‐knockdown led to lower mitochondrial membrane potential (ΔΨm ) and higher reactive oxygen species production in hiPSCs. However, HIF‐1α‐overexpression increased ATP content in hiPSCs, while the role of HIF‐1α‐knockdown was opposite. The embryoid body (EB) and teratoma formation assays showed that HIF‐1α‐knockdown promoted endoderm differentiation and development in vitro and in vivo. In terms of the underlying molecular mechanisms, HIF‐1α‐knockdown inhibited the expression of Actl6a and histone H3K9ac acetylation (H3K9ac). Actl6a knockdown reduced the expression of H3K9ac and the pluripotency of hiPSCs, and also affected endoderm differentiation. These data suggest that hindering HIF‐1α expression causes the changes in mitochondrial properties and metabolic disorders in hiPSCs. Furthermore, HIF‐1α affects hiPSC pluripotency, and germ layer differentiation via Actl6a and histone acetylation.